2016
DOI: 10.1038/srep35596
|View full text |Cite
|
Sign up to set email alerts
|

Marginal evidence for cosmic acceleration from Type Ia supernovae

Abstract: The ‘standard’ model of cosmology is founded on the basis that the expansion rate of the universe is accelerating at present — as was inferred originally from the Hubble diagram of Type Ia supernovae. There exists now a much bigger database of supernovae so we can perform rigorous statistical tests to check whether these ‘standardisable candles’ indeed indicate cosmic acceleration. Taking account of the empirical procedure by which corrections are made to their absolute magnitudes to allow for the varying shap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
216
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(232 citation statements)
references
References 33 publications
14
216
2
Order By: Relevance
“…These authors marginalized latent variables out of their effective likelihood, in an approach similar to our own, although with a number of detailed differences. 12 In particular, the s 1 (marginal posterior) contour obtained with BAHAMAS overlaps closely with the s 1 (profile likelihood) contour in Nielsen et al (2015), while the s 2 contour from BAHAMAS shows a degree of asymmetry that is not present in Nielsen et al (2015). (Recall that the analysis of Nielsen et al (2015) relies on approximating the confidence regions using Gaussians, while the numerical sampling of BAHAMAS does not.…”
Section: Ess( )mentioning
confidence: 99%
See 2 more Smart Citations
“…These authors marginalized latent variables out of their effective likelihood, in an approach similar to our own, although with a number of detailed differences. 12 In particular, the s 1 (marginal posterior) contour obtained with BAHAMAS overlaps closely with the s 1 (profile likelihood) contour in Nielsen et al (2015), while the s 2 contour from BAHAMAS shows a degree of asymmetry that is not present in Nielsen et al (2015). (Recall that the analysis of Nielsen et al (2015) relies on approximating the confidence regions using Gaussians, while the numerical sampling of BAHAMAS does not.…”
Section: Ess( )mentioning
confidence: 99%
“…Nielsen et al (2015). These authors marginalized latent variables out of their effective likelihood, in an approach similar to our own, although with a number of detailed differences.…”
Section: Ess( )mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study [37] using the JLA dataset also showed that by ignoring the velocity covariance may produce a hint of anisotropy from the data. In this context, it is interesting to notice here the result of the work [49] where the authors studied the JLA set, considering all the information from possible systematics (encoded in the covariance) in the analysis, finding a marginal (less than 3σ) evidence for the accepted cosmic acceleration. …”
Section: Analysis Using the Loss Samplementioning
confidence: 99%
“…The ΛCDM model has become the standard cosmological model with the evidence for an accelerated expansion provided by the type Ia supernovae (SNIa) Hubble diagram (Riess et al 1998;Perlmutter et al 1999). However, there has recently been an important discussion in the literature concerning the ability of SNIa data alone to prove the accelerated expansion of the Universe (Nielsen et al 2016;Shariff et al 2016;Rubin & Hayden 2016;Ringermacher & Mead 2016).…”
Section: Introductionmentioning
confidence: 99%